PERAN AKTIVITAS FISIK DAN JUMLAH SHIFT MALAM TERHADAP KUALITAS TIDUR PEGAWAI YANG BEKERJA DI TRANSPORTASI KERETA - Destyana, Patra
Background: Shift worker have disturbed circadian rhythm because irregular sleep. In the transportation sector, they have irregular working hours, unusual resting places and disrupted physical activities. This can worsen sleep quality and have a negative impact on health such as obesity, diabetes, cancer, coronary heart disease and cognitive decline. Exercise may reduce this risk by improve the sleep quality. The purpose of this study was to determine the impact of exercise on the sleep quality of night shift worker in train transportation. Methods: 445 respondents have filled out a physical activity questionnaire (International Physical Activity Questionnaire) and sleep quality (The Pittsburgh Sleep Quality Index Questionnaire) which were then sorted based on inclusion and exclusion criteria so that 186 research subjects were obtained. The data collected was then analyzed by Spearman's Correlation. Results: Statistical tests showed a correlation between the number of night shifts with sleep quality (?=0.205) and physical activity (?=0.187). When viewed per component of sleep quality and physical activity, the number of night shifts correlated with the duration of moderate physical activity (?=0.200), walking activity duration (?=0.224), subjective sleep quality (?=0.216) and sleep latency (?=0.192). In addition, days of vigorous activity was correlated with global sleep quality (?=-0.174) and sleep latency (?=- 0.166), sleep latency was also correlated with the duration of vigorous activity (?=0.154). Conclusion: This study shows that the more days of exercise, the better sleep quality despite having a lot number of night shifts.